2015
DOI: 10.1016/j.juro.2014.09.091
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Study of the Efficacy of Tamsulosin Monotherapy and its Combination with Mirabegron for Overactive Bladder Induced by Benign Prostatic Obstruction

Abstract: Combined tamsulosin and mirabegron treatment is effective and safe for patients with benign prostatic obstruction who have overactive bladder symptoms after tamsulosin monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 16 publications
5
91
2
4
Order By: Relevance
“…Mirabegron has been approved for the treatment of OAB and has been successfully used in combination with a-blockers in patients with concomitant LUTS secondary to BPH and symptoms of OAB [49]. Considering that the oral administration of mirabegron, rather than ICI, may be more tolerable, a clinical study evaluating the potential benefit of oral mirabegron in a subset of patients with LUTS or OAB and concomitant ED could be of benefit to assess its potential for improving erectile function.…”
mentioning
confidence: 99%
“…Mirabegron has been approved for the treatment of OAB and has been successfully used in combination with a-blockers in patients with concomitant LUTS secondary to BPH and symptoms of OAB [49]. Considering that the oral administration of mirabegron, rather than ICI, may be more tolerable, a clinical study evaluating the potential benefit of oral mirabegron in a subset of patients with LUTS or OAB and concomitant ED could be of benefit to assess its potential for improving erectile function.…”
mentioning
confidence: 99%
“…In BOO patients, Nitti et al (2013) found that mirabegron had little effect on OAB symptoms, detrusor pressure at maximum urinary flow, and post-void residual urine, suggesting that mirabegron may have little effect on detrusor function following outlet obstruction in man. Ichihara et al (2015), on the other hand, found that adding mirabegron to a muscarinic receptor blocker improved symptoms and also increased the post-void residual, but the patients in that study, as judged by from maximum urinary flow rates, were less obstructed. It has been reported that β3-adrenoceptor agonists improve bladder storage function, inhibit smooth muscle contractility, experimental hyperreflexia and detrusor instability also in rat BOO (Woods et al, 2001, Michel et al, 2011).…”
Section: Discussionmentioning
confidence: 83%
“…After having been established as a potential valuable treatment for OAB [36][37][38], mirabegron has been tested in men with LUTS/benign prostatic hyperplasia with encouraging results [3]. On the basis of pathophysiological data summarized here above, there may be also some room for phosphodiesterase5 inhibitors for management of residual OAB.…”
Section: Therapeutic Approaches For Residual Overactive Bladder Symptomsmentioning
confidence: 99%
“…In case of voiding symptoms, a-blockers are the first choice, whereas antimuscarinics (or more recently b 3 -adrenergics) are indicated when storage symptoms are predominant. Antimuscarinics and b 3 -adrenergics are also valuable options as an add-on therapy in the absence of improvement of storage symptoms in case of prescription of a-blockers [2,3]. However, many men have persistent bothering symptoms under medical therapy or have progressive disease requiring surgical management.…”
Section: Introductionmentioning
confidence: 99%